Short Communication: Selected medicinal plants in East and North Kalimantan (Indonesia) against Propionibacterium acnes - ENOS TANGKE ARUNG; WHICLIFFE FIERNALEONARDO PASEDAN; IRAWAN WIJAYA KUSUMA; MEDI HENDRA; MERY BUDIARTI SUPRIADI (Biodiversitas Journal of Biological Diversity, 2017)
Abstract. Arung ET, Pasedan WF, Kusuma IW, Hendra M, Supriadi MB. 2017. Short Communication: Selected medicinal plants in East and North Kalimantan (Indonesia) against Propionibacterium acnes. Biodiversitas 18: 321-325. Based on community based research on ethnomedicine local knowledge and medicinal plant in Indonesia by Medicinal Plant and Traditional Medicine Research and Development Center of Indonesian Ministry of Helath in 2012 and 2015, various data on medicinal plants including for cosmetic in all Indonesia region has been collected. There are 38 medicinal plants use for skin care/cosmetics. This study focused on some selected medicinal plants used by several Dayak ethnic groups in East and North Kalimantan, Indonesia for cosmetic, especially for anti-acne. Four plants were selected for evaluating its property on anti-acne, namely Crotalaria pallida, Lepisanthes amoena, Premna corymbosa, and Vitex pinnata by well diffusion and dilution methods. The zone inhibition (mm) against Propionibacterium acnes of these leaves extract on anti-acne at 1000 mg/mL was 9.33; 16.44; 13.78; 11.00 mm, respectively and chlorampenicol (positive control) was 29.44 mm at 500 mg/mL. These results were in line with traditional used by Dayak tribes in East and North Kalimantan, Indonesia. Keywords: Anti acne, cosmetic, medicinal plants, traditional medicine